PENGARUH KUALITAS PRODUK, HARGA, CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DI KFC KOTA PRABUMULIH - Tusri, Yudi; Betriana, Meirani; Adelina, Chairani (Ekonis: Jurnal Ekonomi dan Bisnis, 2023)
This study aims to determine Product Quality on Purchase Decisions at KFC Prabumulih City, to determine Price Against Purchase Decisions at KFC Prabumulih City, and to determine Brand Image Against Purchase Decisions at KFC Prabumulih City, where Tables of Product Quality (X1), Price (X2), Image (X3) and Purchase Decision (Y). with a sample of 75 people. The data management technique used was the SPSS version 22 program. This data was processed using the Normality Test, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test, with the help of the SPSS version 22 application, based on the analysis results obtained the regression equation Y = 7,168+0,379.X1+0,342.X2+0,342.X3+e. By using the regression analysis method, it can be concluded that the variables Product Quality (X1), Price (X2), Image (X3) have a positive and significant effect on Purchase Decision (Y) with a calculated f value of 18.138 with a significance of 0.000 0.05, because a significant value below 0.05 indicates Product Quality, Price and Brand Image have a significant positive influence on purchasing decisions at KFC Prabumulih City.Keywords: Product Quality, Price and Brand Image on Purchasing Decisions